Strategic Entrepreneurials and Brand Trust on Purchasing Decisions Through E-Commerce - Komalawati, Anita; Setiawan, Rahyuniati; Mubarok, Teten Muhamad Sapril (Entrepreneurship Faculty, Universitas Garut, 2024)
Basically, Nature Republic has experienced a significant decline in sales. Where this decline in sales occurred until 2020. The purpose of this study is to analyze business strategies with brand trust in increasing e-commerce for product quality. The research method uses a quantitative approach with a descriptive quantitative research design, data collection techniques using observation, documentation studies and questionnaires. Data analysis techniques use hypothesis testing and regression in identifying the influence between variables. The results of the data analysis can be interpreted that a determination coefficient of 0.533 is obtained. This means that the independent variables, namely product innovation and brand trust, are able to explain the dependent variable, namely purchasing decisions by 53.3% and 46.7% are determined by other factors not studied in this study. Therefore, partially product innovation has a significant influence on purchasing decisions for Nature Republic products through Shopee e-commerce. This is indicated by the results of the t-test calculation which has a value greater than the t table.